The Practice of Glocalization in the Motivate Phase of the Learning Model Design for BIPA Diaspora Learners in Mindanao, Philippines - Yunia Tiara Riski; Hendratno; Wahyu Sukartiningsih; Neni Mariana; Ganes Gunansyah; Suryanti (UIN Raden Mas Said Surakarta, Indonesia, 2026)
Reading motivation is a crucial factor in learning Indonesian for Foreign Speakers (BIPA), particularly in diaspora contexts that face linguistic and cultural challenges. BIPA reading instruction in Mindanao still tends to be linguistically oriented and has not systematically integrated glocalization contexts. This study began with the need to develop a glocalization-based “motivate” phase within the MAGANDA (Motivation, Gleefulness, and Appreciation) learning model to strengthen engagement and reading readiness among diaspora students. This study aims to describe the practice of glocalization in the “motivate” phase in the development of the MAGANDA learning model and its contribution to the reading motivation of BIPA diaspora students in Mindanao. The study used a qualitative research and development (R&D) approach with the 4D model framework. The study focused on the design stage, using a descriptive strategy. Data were obtained through semi-structured interviews, participant observation, and document analysis with teachers, students, and evaluators in the BIPA diaspora community in Mindanao. Data analysis used thematic analysis with source triangulation. The study's results reveal two main findings. First, the practice of glocalization in the “motivate” phase is carried out through the integration of children's songs as cultural bridging, which has been proven to significantly reduce affective barriers (anxiety) and build a sense of national identity closeness. This strategy activates local cultural schemata while introducing the Indonesian language contextually. Second, the “motivate” phase increases student engagement, recognition, and self-efficacy before entering reading activities. Responses from students, teachers, and evaluators indicate increased self-confidence and readiness to learn compared to conventional learning. The integration of glocalization in the initial phase of learning serves as a strategy for managing affective factors in second language acquisition. Thus, the “motivate” phase in the MAGANDA model is not simply an introduction to learning but also serves as a space for initial meaning construction that strengthens the identity, psychological comfort, and cognitive readiness of diaspora students in reading BIPA texts. Motivasi membaca merupakan faktor krusial dalam pembelajaran Bahasa Indonesia bagi Penutur Asing (BIPA), khususnya pada konteks diaspora yang menghadapi tantangan linguistik dan kultural. Pembelajaran membaca BIPA di Mindanao masih cenderung berorientasi linguistik dan belum mengintegrasikan konteks glokalisasi secara sistematis. Penelitian ini berangkat dari kebutuhan pengembangan fase “motivate” berbasis glokalisasi dalam model pembelajaran MAGANDA (Motivation, Gleefulness, and Appreciation) untuk memperkuat keterlibatan dan kesiapan membaca pemelajar diaspora. Penelitian ini bertujuan untuk mendeskripsikan praktik glokalisasi pada fase “motivate” dalam pengembangan model pembelajaran MAGANDA dan kontribusinya terhadap motivasi membaca pemelajar BIPA diaspora di Mindanao. Penelitian menggunakan pendekatan kualitatif research and development (R&D) dengan kerangka model 4D. Fokus penelitian berada pada tahap design dengan strategi descriptive. Data diperoleh melalui wawancara semi-terstruktur, observasi partisipatif, dan analisis dokumen terhadap pamong, pemelajar, dan evaluator di komunitas BIPA diaspora Mindanao. Analisis data menggunakan thematic analysis dengan triangulasi sumber. Hasil penelitian menunjukkan dua temuan utama. Pertama, praktik glokalisasi dalam fase motivate dilakukan melalui integrasi lagu anak sebagai cultural bridging terbukti secara signifikan menurunkan hambatan afektif (anxiety) dan membangun kedekatan identitas nasional. Strategi ini mengaktivasi skema budaya lokal sekaligus memperkenalkan bahasa Indonesia secara kontekstual. Kedua, fase “motivate” berkontribusi pada peningkatan keterlibatan (engagement), pengakuan (recognition), dan efikasi diri (self-efficacy) pemelajar sebelum memasuki aktivitas membaca. Respons pemelajar, pamong, dan evaluator menunjukkan peningkatan rasa percaya diri dan kesiapan belajar dibandingkan dengan pembelajaran konvensional. Integrasi glokalisasi pada fase awal pembelajaran berfungsi sebagai strategi pengelolaan faktor afektif dalam akuisisi bahasa kedua. Fase “motivate” dalam model MAGANDA tidak sekadar pembuka pembelajaran, tetapi menjadi ruang konstruksi makna awal yang memperkuat identitas, kenyamanan psikologis, dan kesiapan kognitif pemelajar diaspora dalam membaca teks BIPA.